The role of idioms in teaching English - Klochkova, L. О.; Клочкова, Л. О. (My University, 2010)
The role of idioms in teaching English has been analyzed. The main groups of idioms have been presented and basic techniques of teaching English idioms have been described
Klochkova, L. О. The role of idioms in teaching English / L. О. Klochkova // Гуманіт. вісн. НУК. – Миколаїв : НУК, 2010. – Вип. 3. – С. 122–124.
Keywords: idiom; teaching; classification; technique; context; ідіома; викладання; класифікація; метод; контекст